Analisis Pengaruh Slogan Yakult terhadap Minat Beli Mahasiswa di Bekasi - Satria, Dwi Wahyu; Nayiroh, Luluatu; Kusumaningrum, Rastri (Innovative: Journal Of Social Science Research, 2025)
Marketing promotion is a mandatory thing to do by business actors, types of marketing promotion are campaigns. The form of campaign promotion can be done by giving a slogan to the product to be marketed as a form of identity as a differentiator from other products. This study aims to analyze the effect of the Yakult slogan on the purchasing interest of students in Bekasi using a quantitative approach and the AIDA theory (Attention, Interest, Desire, Action). The data collection technique was carried out through a questionnaire to 100 student respondents. Data analysis was carried out using simple linear regression and partial tests (t-tests). The results of the study showed that the attention and desire aspects of the slogan had a significant effect on purchasing interest, while the interest and action aspects did not have a significant effect. This finding indicates that the initial attraction and trust in the slogan play an important role in influencing purchasing interest.